407 Phenotypic heterogeneity of COVID-19 pneumonia: clinical and phatophysiologic relevance of the vascular phenotype. (8th December 2021) - Bertini, Matteo; D'Aniello, Emanuele; Di Ienno, Luca; Gibiino, Federico; Tavazzi, Guido; Volta, Carlo Alberto; Contoli, Marco; Papi, Alberto; Campo, Gianluca; Ferrari, Roberto; Rapezzi, Claudio
Abstract: Recent data support the existence of a distinctive 'vascular' phenotype with the involvement of both pulmonary parenchyma and its circulation in COVID-19 pneumonia. Its prompt identification is important for the accurate management of COVID-19 patients. The aim is to analyse the pro and contra of the different modalities to identify the 'vascular' phenotype. Chest computed tomography scan and angiogram may quantify both parenchyma and vascular damage, but the presence of thrombosis of pulmonary micro-circulation may be missed. Increased d -dimer concentration confirms a thrombotic state, but it cannot localize the thrombus. An elevation of troponin concentration nonspecifically reflects cardiac injury. Echocardiogram and electrocardiogram provide specific signs of right ventricular pressure overload. This is particularly relevant for the 'vascular' phenotype which does not necessarily represent the result of thromboembolic venous complications but, more frequently, it is the result of pulmonary microcirculation thrombosis in situ and needs immediate therapeutic action.